If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + y + -3y + 6x = 0 Reorder the terms: 5x + 6x + y + -3y = 0 Combine like terms: 5x + 6x = 11x 11x + y + -3y = 0 Combine like terms: y + -3y = -2y 11x + -2y = 0 Solving 11x + -2y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. 11x + -2y + 2y = 0 + 2y Combine like terms: -2y + 2y = 0 11x + 0 = 0 + 2y 11x = 0 + 2y Remove the zero: 11x = 2y Divide each side by '11'. x = 0.1818181818y Simplifying x = 0.1818181818y
| 12=3(5-x) | | x*x+8x-9=0 | | -10x+4=5x-41 | | 2(x+1)+3x=17 | | 6x-5(3x+4)=7 | | 22x-(9-3x)=41 | | 5x+8=-6x+74 | | .5x^2-x-8=0 | | -(3x+5)=10 | | 13x+4y=60 | | 3+2+4= | | -3x-6=84+7x | | 5x-10=3x-26 | | -4b-4+2b=10 | | -8t-3t+2=-5-6t | | (8a+1)-2a=124 | | 2x-6+7x=-87 | | 6x+10=15+x | | 40x+3y=280 | | 0.66(6x+3)=4x+2 | | -7+x=-5x-31 | | 2x+3(3x-1)=41 | | 40+14y=-2-8y-6 | | 20x+10y=100 | | -41=7x-3x+7 | | 9x-5=-3x+19 | | 4(3-2x)=2(2x+6) | | 16z^2+16z+3=0 | | -7+7x-3x=-39 | | 9x^2+144=0 | | -8(y-10)-15=-2y-(y-5) | | 10y-16=5(2y+4) |